HEGEMONI PEMANGKU KEBIJAKAN BUPATI JEMBER TERHADAP MEDIA MASSA LOKAL: (Analisis Wacana Kritis Terhadap Kebijakan Redaksi JTV Jember) - Nila Noer Karisna (Indonesian Journal of Islamic Communication, 2020)
The mass media which has developed rapidly provides the opportunities for all circles in using and taking the advantage of media for specific purposes, especially for political actors. For example in JTV Jember, one of the media in Jember Regency which reports a local political actor in Jember or the Regent of Jember, positive news that is displayed on JTV Jember has an effect on society. So that the news about the Regent which is negative will not be published because of the collaboration between the Regent of Jember and the media JTV Jember.This study is qualitative with Cresswell's descriptive type of research using purposive subject selection method. The data collection techniques through observation, interviews and documentation. In analyzing the data, the writer uses data reduction, data presentation, and verification.The results of this study reveal that the hegemony carried out by the Regent of Jember towards media JTV Jember is integral or total hegemony because it spontaneously agrees to the provisions of the MOU with the Regent. Further, media JTV Jember does not have freely in reporting the news about the Regent that contains of conflict. In addition, the editorial policy of JTV Jember after being analyzed through text which contains of news representations of JTV Jember becomes a representative in conveying the informations about the Regent of Jember, the relationship between JTV Jember news about the Regent of Jember is motivated by MOU. therefor, the identity of JTV Jember becomes a medium which is known by FaidaTV.